The Orthodox Church and civil society in Russia - Daniel, Wallace L. (Eugenia and Hugh M. Stewart '26 series on Eastern Europe., 2006)
"In the void left by the fall of Communism in Russia during the late twentieth century, can that country establish a true civil society? Many scholars have analyzed the political landscape to answer this question, but in The Orthodox Church and Civil Society in Russia, Wallace L. Daniel offers a unique perspective: within the church are individuals who hold the values and institutional models that can be vital in determining the direction of Russia in the twenty-first century. What the "tireless workers" of the church are doing and whether they will succeed in building a new cultural infrastructure are questions of crucial importance." "Daniel tells the stories of a teacher and controversial parish priest, the leader of Russia's most famous women's monastery, a newspaper editor, and a parish priest at Moscow University to explore thoroughly and with a human voice the transformation from Communist country to a new social order, focusing on normal, everyday realities. Unlike other scholars, who have concentrated on government and politics or looked only within the church's Moscow patriarchy, Daniel explores specific religious communities and the way they operate, their efforts to rebuild parish life, and the individuals who have devoted themselves to such goals. This is the level, Daniel shows, at which the reconstruction of Russia and the revitalization of Russian society is taking place." "This book is written for general readers interested in the intersection between politics, religion, and society, as well as for scholars. The subject and the approach cut across several disciplines: area and cultural studies, history, political science, and religious studies."--Jacket